2004
DOI: 10.1590/s0101-81752004000200004
|View full text |Cite
|
Sign up to set email alerts
|

Relação peso-comprimento de Orthopristis ruber (Cuvier) (Teleostei, Haemulidae) na Baia de Sepetiba, Rio de Janeiro, Brasil

Abstract: A relação peso-comprimento de Orthopristis ruber (Cuvier, 1830) na Baia de Sepetiba (22º54'-23º04'S; 43º34'-44º10'W), Rio de Janeiro foi determinada. Este trabalho objetiva contribuir com o conhecimento sobre a morfometria desta espécie na baía e fornecer bases para comparações com outros ambientes. Os peixes foram coletados em programas de amostragens de arrasto de praia (juvenis) e arrasto de fundo (adultos) entre outubro de 1998 e setembro de 1999. A equação encontrada foi W = 0,000006 L3,1368 para machos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
(2 reference statements)
0
10
0
1
Order By: Relevance
“…The smallest lengths found for Diplectrum radiale (7.5 cm) in Viana et al (2004), Genidens genidens (8.3 cm) in Joyeux et al (2009), Orthopristes ruber (5.5 cm) in Santos et al (2004) were larger than the ones found for these species in Baia Sul (6.3 cm, 4.2 cm and 6.0 cm, respectively). Whereas larger lengths recorded in the literature for Cetengraulis edentulus (17.1 cm) in Joyeux et al (2009), Citharichthys spilopterus (19.0 cm) in Muto et al (2000), Isopisthus parvipinnis (22.8 cm) in Romero et al (2008), Sphoeroides testudineus (26.4 cm) in Joyeux et al (2009), Sphoeroides greeleyi (16.1 cm) in Joyeux et al (2009) and Symphurus tessellatus (16.7 cm) in Joyeux et al (2009) were smaller than the ones recorded in this study (17.2 cm, 19.9 cm, 25.2 cm, 26.0 cm, 28.0 cm, 26.6 cm and 26.1 cm, respectively).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The smallest lengths found for Diplectrum radiale (7.5 cm) in Viana et al (2004), Genidens genidens (8.3 cm) in Joyeux et al (2009), Orthopristes ruber (5.5 cm) in Santos et al (2004) were larger than the ones found for these species in Baia Sul (6.3 cm, 4.2 cm and 6.0 cm, respectively). Whereas larger lengths recorded in the literature for Cetengraulis edentulus (17.1 cm) in Joyeux et al (2009), Citharichthys spilopterus (19.0 cm) in Muto et al (2000), Isopisthus parvipinnis (22.8 cm) in Romero et al (2008), Sphoeroides testudineus (26.4 cm) in Joyeux et al (2009), Sphoeroides greeleyi (16.1 cm) in Joyeux et al (2009) and Symphurus tessellatus (16.7 cm) in Joyeux et al (2009) were smaller than the ones recorded in this study (17.2 cm, 19.9 cm, 25.2 cm, 26.0 cm, 28.0 cm, 26.6 cm and 26.1 cm, respectively).…”
Section: Resultsmentioning
confidence: 76%
“…The comparison of the coefficients of determination (r 2 ) of this and other studies that used the same method of capture (with different mesh sizes) and were carried out, mainly, on the north-northeastern coasts of Brazil (Cordovil & Camargo, 2007;Romero et al, 2008;Freire et al, 2009;Joyeux et al, 2009) and south-southeastern (Giannini & Paiva-Filho, 1990;Bernardes & Rossi, 2000;Haimovici & Velasco, 2000;Muto et al, 2000;Araújo & Vicentini, 2001;Almeida & Branco, 2002;Santos et al, 2004;Viana et al, 2004;Souza-Conceição et al, N: number of individuals; TL: total length; min. : minimum total length; max.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Esses resultados corroboram as observações de Vazzoler (1996), o qual afirma que a proporção sexual em peixes varia ao longo do ciclo de vida em função de eventos sucessivos, que atuam de modo distinto sobre os indivíduos de cada sexo, sendo, na maioria dos casos, a proporção 1:1 observada para a população como um todo. Outros autores também encontraram essa proporção, como os trabalhos apresentados por Dias et al (2004) com Pinirampus pinirampu, Santos et al (2004) com Orthopristis ruber e Silva et al (2005) com Scomberomorus brasiliensis. Por outro lado, Resende et al (1995) mes chegam na barragem de Cachoeira de Emas em março e abril, regionalmente chamados de temporão, e apresentam comprimento médio inferior e estádios não avança-dos de maturação.…”
Section: Figura 2 Fator De Condição Do Curimbatá (Prochilodus Lineatus)unclassified
“…Although publications regarding the LWR for marine tropical species and, in particular, in the Brazilian coast have increased (Araújo et al, 1998;Bernardes & Rossi-Wongtschowski, 2000;Haimovici & Velasco, 2000a, 2000bMuto et al, 2000;Sales & Feitosa, 2000;Frota et al, 2004;Santos et al, 2004;Vianna et al, 2004;Giarrizo et al, 2006), these works are restricted to specific and isolated regions with no comparison among the data.…”
Section: Introductionmentioning
confidence: 99%